Case Report: Adrenocortical adenoma harboring atypical subclinical Cushing’s syndrome with dehydroepiandrosterone sulfate transferase and cytochrome b5 expression in tumor cells - Ichiro Abe; Yuto Yamazaki; Ayuko Higashi; Kentaro Ochi; Keita Kubo; Yuya Fujita; Kaori Takeshita; Toshiaki Wada; Ryo Mitsuoka; Yo Yamashita; Ryoko Yoshida; Tamotsu Kato; et al. (Frontiers in Endocrinology)
Subclinical Cushing’s syndrome (SCS) is frequently encountered during the clinical evaluation of adrenal incidentalomas and is typically associated with reduced levels of serum dehydroepiandrosterone sulfate (DHEA-S). Cytochrome b5 is a component of the electron transfer system that enhances the activity of 17, 20-lyase relative to that of 17a-hydroxylase. Therefore, tumors harboring cytochrome b5 might be associated with dehydroepiandrosterone sulfotransferase (DHEA-ST) expression, resulting in unsuppressed serum DHEA-S levels. Here, we reported the first case of SCS with elevated serum DHEA-S levels in an incidentally detected adrenocortical adenoma showing immunohistochemical positivity for both cytochrome b5 and DHEA-ST.